School Choice Participation Rates: Which Districts are Pressured? - Ni, Yongmei; Arsen, David (Education Policy Analysis Archives, 2011)
School choice policies are intended to provide students in poorly performing schools the option of transferring to a better school. The associated loss of funding to new competitors is expected, in turn, to benefit students who remain in their assigned schools by spurring improved performance among the educators in them. The prospects for such systemic improvement are greatest if in fact student transfers and the market signals they provide are determined by school effectiveness rather than the social and racial characteristics of a district’s students. To test this proposition, we employ a series of fixed effects regressions to analyze the relative influence of school effectiveness versus student demographic composition on participation rates in Michigan’s charter school and inter-district choice policies. Our results indicate that school effectiveness has no systematic influence on participation rates for either choice policy, while the loss of students to choice options increases significantly in districts serving high concentrations of low-income students. Therefore, Michigan’s school choice policies create financial pressures not on schools that are performing most poorly but rather on those that face the most difficult educational challenges.